The Influence of Decoy Effect on Consumer Purchasing Decisions at Starbucks Jakarta - Kurniawati Rina; Tio Prishilla Febriyani Eddy; Saputra Nicko Gana (SHS Web of Conferences, 2024)
The emergence of various new coffee brands, both from within the local and international companies, must think of ways to keep their products afloat amidst the increasingly fierce competition. The aims of this study are: 1) To analyze the differences in consumer purchasing decisions at Starbucks Jakarta before and after applying the decoy effect, and 2) To see the effectiveness of the decoy effect on consumer purchasing decisions at Starbucks Jakarta. The research employs quantitative analysis through an experimental method. The population for this research is the customers who have purchased a Starbucks beverage product at least once and will be applying non-probability purposive sampling. The data collection research used an online questionnaire. Data were then analyzed using the Wilcoxon and N-gain test, which was processed using IBM SPSS Statistic version 25. The results of this study proved that there were changes in consumer decisions before and after the decoy effect was applied based on the Wilcoxon Test, which was carried out with a result of 0.000 <0.05 so that it could be concluded that Ha was accepted, and Ho was rejected. In addition, the decoy effect is also considered quite effective on consumer purchasing decisions based on the N-gain test conducted. The result obtained was 0.68 for the N-gain score, so it is in the medium category, and 68% for the N-gain percent, so it is considered quite effective.